Optimisation of the biological production of levulinic acid in a mixed microbial culture fed with synthetic grape pomace - Correa-Galetote, David; Serrano, Antonio; Ciudad, Gustavo; Pinto-Ibieta, Fernanda (Frontiers in Bioengineering and Biotechnology, 2024)
Levulinic acid (LA) is a polymer with a vast industrial application range and can be co-produced as a minor by-product during the biological production of polyhydroxyalkanoates (PHA). However, the influence of key parameters as tools for favouring the production of LA over PHA is still unclear. In this study, we investigated how several critical operational conditions, i.e., carbon-nitrogen ratio (C/N), organic loading rate (OLR) and airflow, can be optimised to favour LA accumulation over PHA production by a mixed microbial culture (MMC), using synthetic grape pomace (GP) hydrolysate as the substrate. The results showed that it was possible to direct the MMC towards LA accumulation instead of PHA. The maximum LA yield was 2.7 ± 0.2 g LA/(L·d) using a C/N of 35, an airflow of 5 L/min and an OLR of 4 g sCOD/(L·d). The OLR and, to a lesser extent, the C/N ratio were the main factors significantly and positively correlated with the biological synthesis of LA.